HUBUNGAN TINGKAT PENGETAHUAN IBU MULTIPARA DENGAN SIKAP PEMILIHAN ALAT KONTRASEPSI DI DESA NANGGUNGAN KECAMATAN KAYEN KIDUL KABUPATEN KEDIRI - Cahyono, Aris Dwi; Sugiarto, Topan (Akademi Keperawatan Pamenang, 2011)
Family planning is a goverment program which aimed to achieve the welfare of community by performing marital counseling, administering contraceptive agents and planning for childbirth. The fact showed that the choice of contraceptive agens in Indonesia is divergent. The objective of this study was to identify the relationship between the degree of knowledge of multi-child mother and the attitude of contraceptive choice in Nanggungan village, Kayen Kidul Subdistrict, district of Kediri.Research design was cross sectional. Population of study was all multi-child mothers, a number of 429 persons. Sample size was 209 respondents which was choosed by simple random sampling technique. Research variable was the knowledge level and the attitudeÂ in choising contraceptive agents. Data was collected by questionnaire and analyzed bu contingency coefficient test. Result of study showed that there was a strong relationship between the level of knowledge and the attitude in choising the contraceptive agents, with significancy level 0,000 less than 0,05 and the coefficient of relationship was 0,605.Based on the result of study, it is suggested to health care personals to perform health education both in individual (counceling) or mass education as a knowledge base in built a positive attitude when choising the contraceptive agents.Â